Oblicz:
a)-2* 2/3=
3/5* (-4)=
b)-1,2/3=
(-1,6)/(-0,2)=
c) -3/7 / 7=
(-1 i 1/3)*(-0,25)=
zad.2
dla liczb a=(-5) i b= (-9) wpisz wyniki podanych działań.

a+b=(-5)+(-9)=
b-a=
a*b=
(-a)*b=
a-b=
a+(-b)=
a/(-b)=
(-b)/(-a)=


szybko!!!!plisss:)

3

Odpowiedzi

2010-03-08T14:07:44+01:00
1
a)-2* 2/3=-4/3
3/5* (-4)=-12/5=-2 i 2/5
b)-1,2/3=-0,4
(-1,6)/(-0,2)=8
c) -3/7 / 7=-3/49
(-1 i 1/3)*(-0,25)=1/3

2
a=(-5) i b= (-9)

a+b=(-5)+(-9)=-5-9=-14
b-a=-9-5=-14
a*b=-5*(-9)=45
(-a)*b=-(-5)*(-9)=5*(-9)=-45
a-b=-5-(-9)=-5+9=4
a+(-b)=-5+ 9=4
a/(-b)=-5/-(-9)=-5/9
(-b)/(-a)=-(-9)/-(-5)=9/5
1 5 1
Najlepsza Odpowiedź!
2010-03-08T14:17:48+01:00
Zad.1
a)-2* 2/3=-4/3
3/5* (-4)=-12/5=-2 i 2/5
b)-1,2/3=-0,4
(-1,6)/(-0,2)=8
c) -3/7 / 7=-3/49
(-1 i 1/3)*(-0,25)=1/3

zad.2
-14
-14
45
(-45)
4
4
-5/9
9/5


POZDRO:*










2010-03-08T14:28:47+01:00
A)-2* 2/3=-⁴/₃ = -1⅓
3/5* (-4)=-¹²/₅ = -2⅖
b)-1,2/3= -0,4
(-1,6)/(-0,2)= 8
c) -3/7 / 7= -³/₇ * ¹/₇= -³/₁₄
(-1 i 1/3)*(-0,25)= -1⅓ * (-¼) = -⁴/₃ * (-¼)= ⅓
zad.2
dla liczb a=(-5) i b= (-9) wpisz wyniki podanych działań
.

a+b=(-5)+(-9)= -14
b-a=(-9)-(5)=4
a*b=(-5)*(-9)= 45
(-a)*b=-(-5)*(-9)= -45
a-b=(-5)-(-9)=4
a+(-b)=(-5)+-(-9)=4
a/(-b)=(-5)/-(-9)=-⁵/₉
(-b)/(-a)=-(-9)/-(-5)=1,8